Combined isometric and vibration training does not enhance strength beyond that of isometric training alone - Fisher, J.; Van-Dongen, M.; Sutherland, R (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: Research considering combined vibration and strength training is extensive yet results are equivocal. However, to date there appears no research which has considered the combination of both direct vibration and whole-body vibration when used in an isometric deadlift position. The aim of this study was to compare groups performing isometric training with and without direct and whole-body vibration.